Ammonium-free and grain-protection deliming technology with the combination of aromatic sulfonic acid and sodium dihydrogen phosphate in leather manufacture. (10th February 2023) - Zhang, Chunxiao; Liu, Ting; Huang, Baosheng; Zhang, Xu; Peng, Biyu; Mu, Changdao
Abstract: Ammonia-nitrogen, a grave environmental concern, is a typical pollutant in deliming process due to the inclusion of ammonium salts as deliming agents in leather manufacture. In order to reduce the emission of ammonia-nitrogen and improve the biological treatment of mixed tannery wastewater, an ammonium-free deliming method was designed and optimized based on the synergistic effects of aromatic sulfonic acids and sodium dihydrogen phosphate. The results indicated that, the penetrating and buffering performance of the mixtures of p-Hydroxybenzene sulfonic acid (pHBSA) and sodium dihydrogen phosphate (SDHP) at weight ratio of 2:1 was good enough to fulfill the requirement of deliming. The organoleptic and mechanical properties of the crust leather produced by pHBSA-SDHP mixtures deliming were similar with the conventional ammonium sulfate deliming, and the grain pattern was found to be protected against the damage caused by enzymes during bating. The concentrations of ammonia-nitrogen and total nitrogen in pHBSA-SDHP deliming effluent were dramatically cut down by 99% and 94%. It is anticipated that the mixed tannery wastewater could be disposed of more easily by means of adjusting the total organic ratios of C:N:P to their natural ratio by introducing an additional carbon and phosphorus source to the tannery wastewater. This investigation provides an improved method of leather making with significant reduction of ammonia nitrogen emission in deliming operation and fulfills the integral requirements of the modern sustainable leather industry.